Photography as a machine organism: The cyberneticization of the photographic and techne as ethics. (1st December 2015) - Martinez, Mark
This article proposes a cybernetic photographic theory that takes seriously the philosophical claim that cameras, images and human beings exist as evolving systems of machines-organisms. It provides an epistemological challenge to the modernist problematic of representation – namely, the emergence of human consciousness outside and above nature, and a rationalist distinction between an active, visual-reasoning subject and a passive object. I utilize the (non)philosophy of Francois Lauruelle in order to foreground and deepen the understanding of the ethical thought in cybernetics. My purpose is to build upon ethical philosophy that, as Gilbert Simondon contended, would 'save the technical object'. There is some urgency to this task as, in saving machines from their own histories and statuses as non-human, representational things in the world, we may begin an ethico-political programme that evaluates the complementary creative processes of human and machine – in a word, our shared Art – in order to save ourselves. It is perhaps the case that any recuperation of cybernetic and photographic theory today be poised not to reckon with our 'digital' moment but rather with our Anthropocene era defined by human's extinction level powers of destruction.